Darkness calls - Liu, Marjorie M. (Liu, Marjorie M. Hunter Kiss novel., 2009)
"Nomad born and bred, demon hunter Maxine Kiss has always relied upon herself to fight the darkness that surrounds her, the predators--human, zombie, and otherwise--who threaten the earth. But one man has penetrated her lonely life: Grant, the last of his kind. With the ability to manipulate energy, he can control any living creature including demons. And now his life is in danger. Haunted by the past, determined to change the future, Maxine soon understands that to save Grant, she has only one choice--to lose control and release her own powers of darkness."--Page 4 of cover.